2014
DOI: 10.1161/jaha.114.000784
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Kidney Injury for Patients Treated With a High‐Potency Versus Moderate‐Potency Statin Regimen After an Acute Coronary Syndrome

Abstract: BackgroundObservational studies have raised concerns that high‐potency statins increase the risk of acute kidney injury. We therefore examined the incidence of kidney injury across 2 randomized trials of statin therapy.Methods and ResultsPROVE IT‐TIMI 22 enrolled 4162 subjects after an acute coronary syndrome (ACS) and randomized them to atorvastatin 80 mg/day versus pravastatin 40 mg/day. A‐to‐Z enrolled 4497 subjects after ACS and randomized them to a high‐potency (simvastatin 40 mg/day×1 months, then simvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In contrast, previous RCTs have not found a significant association between statin treatment and the risk of AKI, or an excess risk of AKI for high potency vs moderate/low potency regimens [1921]. A recent RCT examined the risk of AKI associated with a short course of atorvastatin 40–80 mg daily during the perioperative period among adult patients receiving cardiac surgery, and found no significant effect overall (HR associated with atorvastatin 1.06 (95% CI 0.78, 1.46)) or among those who were naïve to statin treatment at baseline (HR 1.61, 95% CI 0.86, 3.81)) [22].…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, previous RCTs have not found a significant association between statin treatment and the risk of AKI, or an excess risk of AKI for high potency vs moderate/low potency regimens [1921]. A recent RCT examined the risk of AKI associated with a short course of atorvastatin 40–80 mg daily during the perioperative period among adult patients receiving cardiac surgery, and found no significant effect overall (HR associated with atorvastatin 1.06 (95% CI 0.78, 1.46)) or among those who were naïve to statin treatment at baseline (HR 1.61, 95% CI 0.86, 3.81)) [22].…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, the use of a high-potency statin regimen did not increase the risk of kidney injury was observed in 2 large randomized trials of statin therapy in patients with acute coronary syndrome; PROVE IT-TIMI 22 [50,55] (atorvastatin 80 mg/day) including 4,162 patients, and A-to-Z trial (pravastatin 40 mg/day for 1 month + simvastatin 80 mg/day after 1 month) including 4, 497 patients. [72] As mentioned in the previous section, the ATTEMP (Assessing the treatment Effect in Metabolic syndrome without Perceptible diabetes) study [67] showed that multifactorial intervention in patients with metabolic syndrome without established CVD improved renal function and reduced serum uric acid levels. Of importance, these changes were more prominent in stage 3 chronic kidney diseases patients.…”
Section: Statins May Improve Renal Functionmentioning
confidence: 93%
“…Moreover, two prospective, randomized, controlled trials, the TNT trial (n = 10,001), in patients with stable CHD, and the Pravastatin or Atorvastatin Evaluation and Infection Therapy trial, in patients with acute coronary syndromes (ACS), used the 80 mg/day dose of atorvastatin with beneficial or, in the worst case, neutral effect on renal function; no case of acute renal failure was reported [63,64,82,83]. Besides, the joint analysis of IDEAL, TNT, CARDS, ASPEN, SPARCL, and other statin survival placebo-controlled trials, using high-potency statins, mainly atorvastatin at 80 mg/ day, did not show adverse events related to renal function and especially AKI after 149,882 patient-years of follow-up with high potency statins compared with lower potency statins or placebo [84].…”
Section: Statins and Gfrmentioning
confidence: 99%